Electric field interactions between closely abutting excitable cells. - Sperelakis, N. (IEEE Engineering in medicine and biology magazine)
This review article summarizes some of the electrophysical evidence and morphological evidence against the hypothesis that the myocytes of cardiac muscles and visceral smooth muscles are profusely interconnected by low-resistance pathways (e.g., tunnels or gap-junction channels), which would give rise to a long length constant. Instead, propagation of the action potential (AP) is discontinuous, with a substantial junctional delay time at the cell junctions. Since the entire surface membrane of each cell becomes excited nearly simultaneously, a plot of propagation time versus distance (along a strand of cells) exhibits a typical staircase shape. This article demonstrates that the electric field that develops in the narrow junctional cleft (negative cleft potential) when the prejunctional membrane (pre-JM) fires an AP acts to depolarize the post-JM to its threshold. This mechanism, by itself, can account for transmission of excitation from cell to cell, but accessory mechanisms that act additively include K+ accumulation in the junctional clefts, gap-junction channels, and capacitive coupling